PEMANFAATAN OLI BEKAS HIDROLIK YANG DICAMPUR DENGAN SOLAR TERHADAP EMISI GAS BUANG PADA MESIN DIESEL - Bagus Lutfiwijaya; Akhmad Syarief; Sigit Mujiarto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2018)
Used hydraulic oil SAE 10 is a waste activities that are often found in Indonesia, especially in mining and plantantion scale hydraulic large. Waste used oil SAE 10 can be used as a fuel mixture of hydrocarbons is done by mixing the used oil hydraulic SAE 10 with other fuels such as gasoline, kerosene, diesel fuel with the addition of a maximum percentage of less than 50%. this research tries to investigate exhaust emissions on diesel engines with hydraulic mixing used oil into diesel fuel with a mixture of different variations. The machine used is a four-stroke diesel engine with a maximum power of 4.4 kW. Be based testing has been done variations of a mixture of 5% and 10 % is still within the allowed limits.